Myelodysplastic Syndrome: Raeb-1 in A 58-Year-Old Male: A Case Report from Andhra Pradesh, India - Tamanam, Renu Sri; Puli, Chandrika; Thinnavalli, Theja Sree; Gannamaneni, Abhi Chowdary; Konkimalla, Sri Kumari; Taviti, Ratna Kumari; Devarapalli, Ruth Hepsiba; Yanamadala, Pavan Kumar; Nadendla, Rama Rao (Asian Journal of Biological and Life Sciences, 2026)
Myelodysplastic Syndromes (MDS) represent clonal hematopoietic disorders that are marked by ineffective hematopoiesis, peripheral cytopenias, and a fluctuating risk of progression to acute myeloid leukaemia. Research conducted in India has revealed an earlier age of onset and a greater prevalence of adverse cytogenetic profiles in comparison to Western populations; however, comprehensive case-based documentation is still lacking. We report a case of a 58-year-old male farmer from Guntur District, Andhra Pradesh, who experienced progressive dyspnea, fatigue, recurrent low-grade fever, gum bleeding, and spontaneous bruising. Examination revealed pallor, petechiae, and mild splenomegaly. Laboratory tests showed pancytopenia with macrocytic anaemia, hypogranular neutrophils, and giant platelets. Bone marrow aspiration indicated hypercellularity with multilineage dysplasia, ring sideroblasts, and 6% myeloblasts. Cytogenetic analysis revealed an isolated deletion of chromosome 5q. Based on these findings, a diagnosis of MDS - Refractory Anaemia with Excess Blasts-1 (RAEB-1) was made. The patient was treated with supportive transfusions, empirical antibiotics for febrile neutropenia, and subcutaneous azacitidine. This case exemplifies the diversity of MDS, consistent with Indian research that indicates an earlier onset and differing prognostic characteristics. It underscores the importance of documenting individual cases to connect epidemiological disparities between Western and Indian populations. This case underscores the clinical and cytogenetic characteristics of MDS in an Indian patient, drawing attention to the diagnostic difficulties and treatment considerations in settings with limited resources. Comprehensive regional case reports are crucial for enhancing the understanding of disease biology and outcomes within Indian populations.
Keywords: Myelodysplastic Syndromes; Chromosome 5q Deletion Syndrome; Bone Marrow; Dysplasia; Hematologic Neoplasms; Macrocytic Anaemia; Supportive Care